CRIMINAL RESPONSIBILITY OF CHILDREN IN BRAWLS THAT RESULTED IN DEATH IN REVIEW OF LAW NUMBER 35 OF 2014 (STUDY OF DECISION PN TANJUNG KARANG NUMBER 11/PID.SUS-ANAK/2025/PN TJK) - Benny Karya Limantara; Carissa Novira Putri (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Student brawls involving children remain a recurring social phenomenon in Indonesia and frequently result in serious criminal offenses, including those causing death. Children as perpetrators of criminal acts occupy a special position within the criminal justice system; therefore, their criminal liability cannot be equated with that of adults. This study aims to analyze the criminal liability of children involved in brawls resulting in death and to examine the application of legal provisions in the Decision of the Tanjung Karang District Court based on the Child Protection Act and the Juvenile Criminal Justice System. The research employs normative juridical and empirical juridical approaches through the study of statutory regulations, analysis of court decisions, and interviews with law enforcement officers. The data were analyzed qualitatively to describe the implementation of juvenile criminal law. The findings indicate that child offenders may still be held criminally liable while observing the principle of the best interest of the child. Judges consider both juridical and non-juridical aspects, including the child’s role in the offense, age, psychological condition, and social inquiry reports, resulting in sanctions that emphasize rehabilitation rather than retribution. This study concludes that the application of juvenile criminal law in cases of brawls resulting in death is in accordance with prevailing legal provisions; however, improvements in the quality of case handling by law enforcement agencies are still necessary to ensure balanced and sustainable child protection and justice for victims.